SPONTANEOUS PORTOSYSTEMIC SHUNTS: RELATIONSHIP TO UPPER GASTROINTESTINAL BLEEDING AND HEPATIC ENCEPHALOPATHY - Atilla ÖKTEN; Sabahattin KAYMAKOĞLU; Süleyman YALÇIN; Oktay YEĞİNSU; Fatih BEŞIŞIK; Arif ACAR; Güngör BOZTAŞ; Yılmaz ÇAKALOĞLU; Zeynel MUNGAN; Sadakat ÖZDİL (Turkish Journal of Gastroenterology, 2020)
-